1999
DOI: 10.1017/s0022215100143373
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile angiofibroma: the lessons of 20 years of modern imaging

Abstract: Seventy-two patients with juvenile angiofibroma have been investigated by computerized tomography (CT) and/or magnetic resonance imaging (MRI) over a period of 20 years. The evidence from these studies indicates that angiofibroma takes origin in the pterygo-palatine fossa at the aperture of the pterygoid (vidian) canal. An important extension of the tumour is posteriorly along the pterygoid canal with invasion of the cancellous bone of the pterygoid base, and greater wing of the sphenoid (60 per cent of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
150
1
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 11 publications
5
150
1
10
Order By: Relevance
“…He also concluded that most of the tumors can be removed by the traditional/modifi ed transpalatal and lateral rhinotomy approach. Lloyd et al [8] studied 72 juvenile angiofi broma patients with computerized tomography (CT) and/or magnetic resonance imaging (MRI) over a period of 20 years. Their study indicated that angiofi broma takes origin in the pterygopalatine fossa at the aperture of the pterygoid (vidian) canal and extends posteriorly along the pterygoid canal with invasion of the cancellous bone of the pterygoid base and greater wing of sphenoid (60%).…”
Section: Discussionmentioning
confidence: 99%
“…He also concluded that most of the tumors can be removed by the traditional/modifi ed transpalatal and lateral rhinotomy approach. Lloyd et al [8] studied 72 juvenile angiofi broma patients with computerized tomography (CT) and/or magnetic resonance imaging (MRI) over a period of 20 years. Their study indicated that angiofi broma takes origin in the pterygopalatine fossa at the aperture of the pterygoid (vidian) canal and extends posteriorly along the pterygoid canal with invasion of the cancellous bone of the pterygoid base and greater wing of sphenoid (60%).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed history followed by thorough clinical examination of head and neck region was done. The patients were staged both clinically and radiologically prior to surgical treatment using Radkowski et al [4] and Sessions et al [5,6] classification of staging respectively. The patients were advised to undergo preoperative arterial embolization prior to surgery.…”
Section: Methodsmentioning
confidence: 99%
“…13 Endoscope surgery has no major morbidity, no scars, no injuries to nerves and vasculature, and no facial developmental problems. In addition, the length of postoperative hospital stay is significantly shorter than open approaches.…”
Section: Discussionmentioning
confidence: 99%